2020
DOI: 10.1016/j.jtcme.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Chinese herbs in the treatment of fatty liver diseases

Abstract: Eating habits and lifestyle directly impact general health. Consumption of fat- and sugar-rich foods and alcohol increase the risk of developing fatty liver disease. The prevalence of fatty liver disease is markedly critical, and its pathogenesis and progression are complicated. Chinese herbal medicine has been used to treat and prevent human diseases through-out history, and is a rich source of biologically active substances with unique curative properties. More recently, Chinese herbs and their extracts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…In recent years, TCM and its extracts have been considered a new potential source of therapeutic drugs for preventing and treating fatty liver disease [80]. According to modern TCM theory, type 2 diabetes belongs to the category of diabetes.…”
Section: Tcm Syndrome Types Of T2dm With Nafldmentioning
confidence: 99%
“…In recent years, TCM and its extracts have been considered a new potential source of therapeutic drugs for preventing and treating fatty liver disease [80]. According to modern TCM theory, type 2 diabetes belongs to the category of diabetes.…”
Section: Tcm Syndrome Types Of T2dm With Nafldmentioning
confidence: 99%
“…Therefore, finding effective treatment with minimal side effects is essential. Medicinal plants and their constituents have multiple protective and therapeutic effects, so they are widely used to treat diseases and their complex complications, including metabolic diseases such as NAFLD (Francini‐Pesenti, Spinella, & Calò, 2019; Panyod & Sheen, 2020). However, medicinal plants and natural compounds as complementary and alternative therapeutics and conventional restorative therapy reduce the dose of chemical drugs with high side effects and increase their effectiveness (Čabarkapa et al, 2016; Rafieian‐Kopaei, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…31,32,33 Recently, allicin was reported to exhibit a modulatory effect on the gut microbiota and reduced hepatic steatosis. 34,35 Additionally, our previous pilot study showed that allicin supplementation shaped the gut microbiota composition and reduced TMAO production by the gut microbiota in mice subjected to moderate carnitine consumption (0.02 %carnitine). 36 However, the role of raw garlic with allicin in improving cardiovascular phenotypes via gut microbiota modulation has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 98%